A study of radon regulation and pathology as it relates to underground hardrock mining - D. M. Loring (Society for Mining, Metallurgy & Exploration, 2009)
Radon progeny have been a health and safety concern for miners since the mining of radioactive minerals began. Through the ?nuclear age?, it has become better understood and the regulations have become more robust. Ventilation and control practices have improved, thus reducing miners? exposures. This paper provides an overview of radon in mining, the progress of the regulations, and discusses some of the uranium miner studies that contributed to the knowledge of the pathology of radon.